Digital Labour: Digital Capitalism and the Alienation of YouTube Content Creators - Panji Mulkillah Ahmad; Indi Hikami; Biko Nabih Fikri Zufar; Appridzani Syahfrullah (Journal of Asian Social Science Research, 2021)
YouTube is a digital platform that allows content creators to stream their videos in exchange for money earned through the YouTube Partner Program mechanism, motivates many people to join YouTube. However, what they do not realize is the hidden effect YouTube brings in the form of alienation experienced by YouTube content creators as digital labour. This article discusses this phenomenon of alienation experienced by digital labours. Using a qualitative approach with a descriptive research design, it offers a narrative research strategy to examine the narrative and discourse of alienation of content creators on YouTube. The unit of analysis of the study is the content of YouTube creators as digital labour. The findings show that YouTube is mainly a vehicle used by digital capitalism for the sake of profit accumulated by exploiting content creators from the videos they make. Content creators receive disproportionate or even no financial compensation from YouTube for the videos they produce for YouTube. As a result, YouTube content creators as digital labour experienced alienation from their work, their work activities, from themselves as a human species and from other humans.